Human adaptive thermal comfort inside naturally ventilated buildings for religious practice in Thailand - Srithongchai, Thanun (2019)
The adaptive model of thermal comfort considers non-thermal variables as mediators and moderators which can vary building users’ thermal perception. Therefore, the adaptive approach has drawn global attention from researchers due to its potential to reduce energy requirements in buildings. In tropical climates such as Thailand, characterised by high heat and humidity, architectural solutions generally focus on passive shading and cooling techniques utilising ventilation. Although many studies have surveyed various types of buildings, there is a lack of attention to religious buildings, despite extended hours of indoor thermal exposure affecting users’ wellbeing and practice qualities. This research considers adaptive thermal comfort in Buddhist meditation buildings in the tropical climate of Thailand, with particularly consideration of the physiological and psychological benefits of meditative activities, and the sense of space, in the context of an inherited rich Buddhist culture with regard to users’ thermal perception. This field survey, which employed qualitative and quantitative research methods, collected 517 datasets from three Thai meditation buildings from 2016 to 2017. The main aims of this research are to: (i) explore a suitable thermal environment; (ii) examine if the neutral temperature (Tn) is perceived as thermal comfort; and (iii) to investigate users’ most performed thermal adaptive solutions in meditation halls. The findings indicate that the subjects have more extensive ranges of thermal acceptability with a more exceptional adaptive ability than considered in the ASHRAE standards. Additionally, the results demonstrate that the current Tn state is capable of providing the subjects with thermal comfort, but it is not the most comfortable temperature in order to experience enhanced meditative qualities, and subjects performed a combination of adaptions. Thermal sensation votes were affected by non-thermal factors, including meditation experiences and ventilation profiles.